ANALISIS HEADLOSS PADA JARINGAN PERPIPAAN DISTRIBUSI AIR BERSIH DI PERKEBUNAN MARINA KOTA BATAM - Gumilang, Reno Reza; Asmarawati, Citra Indah (LPPM Universitas Putera Batam, 2023)
The rapid population growth will be directly proportional to the need for clean water, so that sooner or later various problems will arise in fulfilling the need for clean water. Marina Plantation, which is located in the city of Batam, is an area where the majority of the population work as gardeners and breeders. The increase in population and the expansion of the plantation area have resulted in a decrease in the burden on the clean water network. In this study the method used is a quantitative method using the Darcy Weisbach calculation formula with the help of Excel software to simplify calculations. Based on the head loss calculation. The technical specifications of the existing pumps are designed only to pump water with a capacity of 4 m3/h with a head of 12 m. To ensure that the existing pumps are no longer able to meet the current water demand. it is necessary to design a pump with a capacity of 10,314 m3/h +30% with a head of 19 m, and further analysis is needed, for example calculating the required pump driving force and the NPSH available in the installation.